Holocene climate variability of the Western Mediterranean: Surface water dynamics inferred from calcareous plankton assemblages - Bazzicalupo, P; Maiorano, P; Girone, A; Marino, M; Combourieu-Nebout, N; Pelosi, N; Salgueiro, E; Incarbona, A (The Holocene, 2020)
A high-resolution study (centennial scale) has been performed on the calcareous plankton assemblage of the Holocene portion of the Ocean Drilling Program Site 976 (Alboran Sea) with the aim to identify the main changes in the surface water dynamic. The dataset also provided a seasonal foraminiferal sea surface water temperatures (SSTs), estimated using the modern analog technique SIMMAX 28, and it was compared with available geochemical and pollen data at the site. Three main climate shifts were identified as (1) the increase in abundance of Syracosphaera spp. and Turborotalita quinqueloba marks the early Holocene humid phase, during maximum summer insolation and enhanced river runoff. It is concomitant with the expansion of Quercus, supporting high humidity on land. It ends at 8.2 ka, registering a sudden temperature and humidity reduction; (2) the rise in the abundances of Florisphaera profunda and Globorotalia inflata, at ca. 8 ka, indicates the development of the modern geostrophic front, gyre circulation, and of a deep nutricline following the sea-level rise; and (3) the increase of small Gephyrocapsa and Globigerina bulloides at 5.3 ka suggests enhanced nutrient availability in surface waters, related to more persistent wind-induced upwelling conditions. Relatively higher winter SST in the last 3.5 ka favored the increase of Trilobatus sacculifer, likely connected to more stable surface water conditions. Over the main trends, a short-term cyclicity is registered in coccolithophore productivity during the last 8 ka. Short periods of increased productivity are in phase with Atlantic waters inflow, and more arid intervals on land. This cyclicity has been related with periods of positive North Atlantic Oscillation (NAO) circulations. Spectral analysis on coccolithophore productivity confirms the occurrence of millennial-scale cyclicity, suggesting an external (i.e. solar) and an internal (i.e. atmospheric/oceanic) forcing.